Fostering FAIR and open sata in South American archaeology : the argentinean case - Izeta, Andrés Darío (2019)
Fil: Izeta, Andrés Darío. Universidad Nacional de Córdoba. Facultad de Filosofía y Humanidades. Departamento de Antropología; Argentina.